Development of bovine-specific cytokine reagents at ILRAD - Mertens, B.; Gaidulis, L.; Mwangi, S.; Suliman, H.; Taylor, K.A. (International Laboratory for Research on Animal Diseases, 1995)
Infection of livestock with African trypanosomes leads to haematological changes such as anaemia and pancytopenia and to immune defects, including suppression of T-cell responsiveness and an excessive increase in the CD5+ B-cell population in blood and spleen. It has been shown that certain breeds of cattle have evolved mechanisms to reduce the effects of trypanosome infections. At ILRAD, trypanosome-specific immune responses of trypanotolerant N'Dama cattle (Bos taurus) are being compared with those of trypanosusceptible Boran (Bos indicus) cattle. The molecular and cellular basis of trypanotolerance are poorly defined, but preliminary data suggest that differences exist between these breeds at the level of T- and B-cell responses to trypanosome antigens during infection. Clear differences have been reported between N'Dama and Boran cattle in the quantity, quality and specificity of antibodies produced following trypanosome infection. Further characterization of these differences and evaluation of their role in trypanotolerance will require the availability of reagents for the analysis of bovine cytokine responses.